2020
DOI: 10.1177/0020294019890627
|View full text |Cite
|
Sign up to set email alerts
|

An improved magnetometer calibration and compensation method based on Levenberg–Marquardt algorithm for multi-rotor unmanned aerial vehicle

Abstract: In order to improvethe yaw angle accuracy of multi-rotor unmanned aerial vehicle and meet the requirement of autonomous flight, a new calibration and compensation method for magnetometer based on Levenberg–Marquardt algorithm is proposed in this paper. A novel mathematical calibration model with clear physical meaning is established. “Hard iron” error and “Soft iron” error of magnetometer which affect the yaw accuracy of unmanned aerial vehicle are compensated. Initially, Levenberg–Marquardt algorithm is appli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 20 publications
1
8
0
Order By: Relevance
“…The key difference in Springmann's method [35] is to estimate the nine θ parameters in two separate minimization steps, as Wu et al demonstrated in [36]. We found that this two-step approach gave more consistent results for another magnetometer (not used in this work) on our UAV.…”
Section: Magnetometer Calibrationsupporting
confidence: 51%
See 1 more Smart Citation
“…The key difference in Springmann's method [35] is to estimate the nine θ parameters in two separate minimization steps, as Wu et al demonstrated in [36]. We found that this two-step approach gave more consistent results for another magnetometer (not used in this work) on our UAV.…”
Section: Magnetometer Calibrationsupporting
confidence: 51%
“…To calibrate the vehicle's magnetometer, we use the model and iterative least squares solver from [35] along with the two-step calibration procedure from [36]. The magnetometer model from [35] is repeated here…”
Section: Magnetometer Calibrationmentioning
confidence: 99%
“…It is more robust than the Gauss-Newton (GN) algorithm. The Levenberg-Marquardt algorithm combines two numerical optimization algorithms: the Gradient Descent (GD) method and the Gauss-Newton (GN) method [ 41 , 42 , 43 ]. To obtain the most precise coefficients without using a highly accurate turntable system, the triaxial accelerometer should be placed continuously and fixed to cover the entire surface of the sphere, and the accelerometer should be influenced only by gravity during the experiment.…”
Section: Calibration Methodsmentioning
confidence: 99%
“…It is more robust than the Gause-Newton (GN) algorithm. The Levenberg-Marquardt algorithm combines two numerical optimization algorithms: the Gradient Descent (GD) method and the Gauss-Newton (GN) method [34][35][36]. To obtain the most precise coefficients without using a highly accurate turntable system, the triaxial accelerometer should be placed continuously and fixed to cover the entire surface of the sphere, and the accelerometer should be influenced only by gravity during the experiment.…”
Section: Levenberg-marquardt Algorithmmentioning
confidence: 99%